Kepemimpinan Kepala Sekolah Dalam Pelaksanaan Manajemen Berbasis Sekolah Di SMP Negeri 1 Baturetno Kabupaten Wonogiri - PRAMONO, Joko, Prof. Dr. Bambang Sumardjoko, Dra. Hariyatmi, M.Si (2015)
The problem studied in this research are as follows: (1) how school leadership in the implementation of school-based management in SMP Negeri 1 Baturetno? (2) How are principals in improving the implementation of school-based management in SMP Negeri 1 Baturetno? (4) How does the achievement of school-based management in SMP Negeri 1 Baturetno ? (5) What factors inhibiting the principal's leadership in the implementation of school-based management in SMP Negeri 1 Baturetno? This research was conducted in SMP Negeri 1 Baturetno 2012/2013 school year. This study used a qualitative research approach. The informants are principals, vice-principals, teachers, school committees and students of SMP Negeri 1 Baturetno. The technique of collecting data using interviews, observasi and documentation. Analysis of the data using an interactive model. The conclusions of this study are as follows: (1) the principal's leadership in the implementation of school-based management in SMP Negeri 1 Baturetno, includes components of curriculum and instructional programs, staff, student, education infrastructure, finance, management, school and community relations and special services management education institutions. (2) Efforts to improve the performance of principals in school-based management in SMP Negeri 1 Baturetno, including delegation and distribution of authority, decisionmaking, policy-setting process, developing communication patterns, supervise and motivate and build a conducive working atmosphere. (3) Access the implementation of school-based management in SMP Negeri 1 Baturetno, include: improving the quality, independence, participation and transparency. (4) Factors that inhibit the principal's leadership in the implementation of schoolbased management in SMP Negeri 1 Baturetno, including the role of society, not all teachers are able to implement school policies, yet the growing culture of quality, bureaucratic and political mechanisms that are less directional .